2007
DOI: 10.1161/01.str.0000251792.76080.45
|View full text |Cite
|
Sign up to set email alerts
|

The Real Estate Factor

Abstract: Background and Purpose-The severity of the neurological deficit after ischemic stroke is moderately correlated with infarct volume. In the current study, we sought to quantify the impact of location on neurological deficit severity and to delineate this impact from that of volume. Methods-We developed atlases consisting of location-weighted values indicating the relative importance in terms of neurological deficit severity for every voxel of the brain. These atlases were applied to 80 first-ever ischemic strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 9 publications
1
70
0
Order By: Relevance
“…While infarct size and location are important, they together explain only half of the variability in functional outcome in patients with ischemic stroke. 24 Our data suggest that the brain's intrinsic capacity to recover from ischemic brain injury may be in part determined by the extent of leukoaraiosis, which is also known to contribute to the variability in outcome. 6 -9 Pathology findings in leukoaraiosis include, among other things, axonal changes ranging from mild demyelination to severe axonal disruption.…”
Section: Standard Protocol Approvals Registrations and Patient Consmentioning
confidence: 74%
“…While infarct size and location are important, they together explain only half of the variability in functional outcome in patients with ischemic stroke. 24 Our data suggest that the brain's intrinsic capacity to recover from ischemic brain injury may be in part determined by the extent of leukoaraiosis, which is also known to contribute to the variability in outcome. 6 -9 Pathology findings in leukoaraiosis include, among other things, axonal changes ranging from mild demyelination to severe axonal disruption.…”
Section: Standard Protocol Approvals Registrations and Patient Consmentioning
confidence: 74%
“…Superficial compartments of the MCA territory, which are also reached by collateral blood flow through leptomeningeal arteries, were also spared from infarction in most patients, although involved in the acute perfusion lesion. Previous studies have used regional information on ischemic lesion distribution to generate maps of topographic lesion distribution (Phan et al, 2009), to correlate infarct location with stroke severity (Menezes et al, 2007), and to generate statistical outcome parameters on a voxelwise analysis (Wu et al, 2006). Our study exceeds previous digital maps Figure 2 Shows the probabilistic distribution of the six-lesion ROI in a standard MNI space superimposed on a mean image of spatially normalized nondiffusion-weighted (b = 0) images of patients with failed (left side, n = 13) and successful (right side, n = 18) recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was shown that the incorporation of infarct location data into volumebased models of functional outcome significantly improved the correlation between imaging-derived severity scores and the observed NIHSS scores. 2 In our study, rather than modeling tissue outcome per se, as in much of the perfusion imaging literature ("core" vs "penumbra" vs "benign oligemia"), 4 we determined the recoverable function of the stroke patient. We could determine the relationship between specific spatial patterns of brain ischemia, and the probability of subsequent motor improvement.…”
Section: Predicting Left Leg Motor Deficit Improvementmentioning
confidence: 99%
“…The precise spatial localization of cerebral hypoperfusion can substantially contribute to the accuracy of predictive models of stroke outcome, especially when used in combination with other clinical information. 2 In present study, we combined admission clinical and topographic hemodynamic imaging data to develop prognostic models for prediction of early functional improvement in acute stroke patients presenting with single extremity motor deficits. An automated location-weighted atlas-based methodology was used to quantify the effects of the complex spatial pattern of admission cerebral perfusion deficits on early functional outcome.…”
mentioning
confidence: 99%